THE EFFECTIVENESS OF PUZZLE GAMES IN STIMULATING PROBLEM SOLVING ABILITY IN EARLY CHILDHOOD - Novi Cynthia Yusnita (Sean Institute, 2023)
The problem in this study is that many children have given up on doing something without trying it first. Children are not brave in solving existing problems. This will certainly affect the life of children in the future. The purpose of this study was to determine the effectiveness of puzzle games in stimulating early childhood problem-solving abilities. The research method used in this study is qualitative with a descriptive type, namely research that provides an overview of the observed object or research focus. Data collection techniques used in this study were observation, interviews and documentation at RA Al-Hidayah. The results and analysis of this study are that children are able to solve problems on their own without help from the teacher. The processes carried out by children in solving problems are understanding and analyzing, designing and planning solutions, finding solutions to problems, and examining solutions. So that way it is very effective in doing puzzle games to stimulate problem solving abilities in early childhood.